1988
DOI: 10.1002/j.1460-2075.1988.tb02805.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of HIV-specific RNase H by monoclonal antibody.

Abstract: Human immune deficiency virus (HIV) replicates by conversion of the RNA genome into the double‐stranded DNA provirus. The reverse transcriptase is not the only enzymatic function crucial in DNA‐provirus synthesis. A viral‐coded RNase H activity which specifically degrades RNA in RNA‐DNA hybrids has been shown to be essential as well. Here we demonstrate that the HIV‐reverse transcriptase which consists of a two‐polypeptide complex, p66 and p51, copurifies with an RNase H activity which exhibits properties of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
170
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 23 publications
7
170
3
Order By: Relevance
“…In addition, a 15-kDa fragment was not detected in disrupted virions by immunoblotting. Hansen et al (1988) have reported detecting a 15-kDa RNase H activity in immunoprecipitates from extracts of HIV-l virions. We are in the process of investigating this apparent discrepancy.…”
Section: Proteolytic Digestion Of Hiv-1 Rtmentioning
confidence: 99%
“…In addition, a 15-kDa fragment was not detected in disrupted virions by immunoblotting. Hansen et al (1988) have reported detecting a 15-kDa RNase H activity in immunoprecipitates from extracts of HIV-l virions. We are in the process of investigating this apparent discrepancy.…”
Section: Proteolytic Digestion Of Hiv-1 Rtmentioning
confidence: 99%
“…First, RT uses the viral RNA genome as a template and a host-cell transfer RNA as a primer to synthesize a minus-strand DNA, producing an RNA-DNA hybrid [5][6][7] . This duplex becomes the substrate of the RNase H domain of RT, which cleaves the RNA strand at numerous points, leaving behind short RNA segments hybridized to the nascent DNA [8][9][10] . Among these RNAs, two specific purine-rich sequences, known as the polypurine tracts (PPTs), serve as unique primers to initiate the synthesis of plus-strand DNA [11][12][13] , thereby creating the double-stranded DNA viral genome.…”
mentioning
confidence: 99%
“…The native enzyme has DNA polymerase and RNase H activities and exists as a heterodimer containing polypeptides of approximately 66 and 5 1 kDa (DiMarzo-Veronese et al, 1986; Lightfoote et al, 1986). The p66 subunit contains both the DNA polymerase and RNase H functional domains, whereas the smaller polypeptide, p51, lacks the carboxyl-terminal RNase H domain (Hansen et al, 1988). RT and the viral DNA integration protein are synthesized as part of the gag-pol precursor polyprotein (for review see, *This paper is dedicated to the memory of Dean L. Richard.…”
mentioning
confidence: 99%